Abrasion resistance of ductile iron austempered by the two-step process - Francucci, Gaston Martin (2008)
The present work focuses in the study of the effect that a new two-step austempering heat treatment process, developed by Putatunda, has on the mechanical properties with emphasis on the response to the abrasive wear. A ductile cast iron melt was prepared in an industrial facility obtaining both, Y-blocks (ASTM A 897) to be used for the laboratory tests samples, and bucket tips to perform field tests by using a wheel loader. The results show that the two-step austempering process promotes an increase in the amount of retained austenite which in turn improves most of the mechanical properties, such as ultimate stress, yield stress, hardness and impact toughness. Two different abrasion tests were carried out in order to evaluate the material response to different tribosystems. The dry sand-rubber wheel abrasion test (ASTM G 65) was used at the lab, where the results show better wear resistance for the two-stepped ADI in comparison with conventional ADI. On the other hand, the bucket tips tested in a more severe environment, showed an opposite tendency.